2016
DOI: 10.1371/journal.pone.0167547
|View full text |Cite
|
Sign up to set email alerts
|

A General Method for Targeted Quantitative Cross-Linking Mass Spectrometry

Abstract: Chemical cross-linking mass spectrometry (XL-MS) provides protein structural information by identifying covalently linked proximal amino acid residues on protein surfaces. The information gained by this technique is complementary to other structural biology methods such as x-ray crystallography, NMR and cryo-electron microscopy[1]. The extension of traditional quantitative proteomics methods with chemical cross-linking can provide information on the structural dynamics of protein structures and protein complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 28 publications
1
78
0
1
Order By: Relevance
“…In the current study we identified crosslinked sites between murine POLRMT and the mitochondrial translation initiation factor IF-2 that are consistent with these proposed secondary functions (70). Last, each of the cross-linked peptide pairs identified here has the potential to serve as a molecular probe for the future study of dynamic in vivo protein conformations and interactions (35,71).…”
Section: Protein Sitesupporting
confidence: 73%
See 2 more Smart Citations
“…In the current study we identified crosslinked sites between murine POLRMT and the mitochondrial translation initiation factor IF-2 that are consistent with these proposed secondary functions (70). Last, each of the cross-linked peptide pairs identified here has the potential to serve as a molecular probe for the future study of dynamic in vivo protein conformations and interactions (35,71).…”
Section: Protein Sitesupporting
confidence: 73%
“…First, we generated two databases to enable (i) targeted quantitative analysis of protein-protein relationships by parallel reaction monitoring (PRM) (71) and (ii) large-scale identification of new datasets by spectral matching (Fig. S7) (27,72).…”
Section: Protein Sitementioning
confidence: 99%
See 1 more Smart Citation
“…XL-MS technology is a powerful and effective structural tool because it offers several layers of information through the identification of cross-linked peptides 4,6,7,23,38,79,138,139 . Within a given protein complex, cross-linking analysis identifies proximal residues between subunits of protein complexes, providing clues on spatial orientation and protein connectivity.…”
Section: Xl-ms Strategies For Structural Analysis Of Protein Complmentioning
confidence: 99%
“…Until now, only a limited number of in vivo XL-MS studies have been reported, mainly due to the challenges discussed above. While the Bruce lab has focused on in vivo cross-linking at the proteome level using their PIR cross-linkers 40,77,89,104106,108,139,151 , our lab has mostly focused on in vivo XL-MS analysis of protein complexes 79,99,159,162,166,167 . Recently, we have developed a membrane permeable, sulfoxide-containing MS-cleavable and enrichable NHS ester cross-linker Azide-A-DSBSO (Table 2) 79 .…”
Section: Xl-ms Strategies For Structural Analysis Of Protein Complmentioning
confidence: 99%